Northern lights - Pullman, Philip, 1946- (London : Scholastic, 2011)
"Without this child, we shall all die." Lyra Belacqua and her animal daemon live half-wild and carefree among scholars of Jordan College, Oxford. The destiny that awaits her will take her to the frozen lands of the Arctic, where witch-clans reign and ice-bears fight. Her extraordinary journey will have immeasurable consequences far beyond her own world...
Formerly CIP.
Keywords: Belacqua, Lyra (Fictitious character) -- Fiction; Fantastic fiction; Young adult fiction